Smallest Meaningful Pay Increases: Field Test, Constructive Replication, and Extension. Issue 1 (6th March 2015) - Mitra, Atul; Tenhiälä, Aino; Shaw, Jason D.
Abstract : The authors extend prior literature by examining, in two distinct field settings, smallest meaningful pay increases (SMPIs) in terms of magnitude, behavioral intention, and affective reactions. In Study 1, a two‐wave study of 177 employees of a university medical center in the United States, the authors find stable thresholds of about 5.0 percent for positive reactions to pay increases (magnitude [5.4 percent], behavioral intentions [4.2 percent], and affective reactions [5.6 percent]). In Study 2, a sample of 495 university employees in Finland, the authors also find stable but slightly higher thresholds of about 8 percent for behavioral intentions (8.4 percent) and positive affective reactions (7.2 percent) to pay increases. They also find threshold effects of −5.7 percent for behavioral intentions and −5.8 percent for negative affective reactions in response to restricted future pay increases levied in the transition to a new pay system. Discussion of the results centers on pay raise administration and future research regarding implied and direct pay reductions. © 2015 Wiley Periodicals, Inc.